SAT0205 Comparison of disease status in uk patients with ra receiving tnfi vs cdmard. (12th June 2018) - Addison, J.; Lobosco, S.; Hoskin, B.; Sullivan, E.; Pike, J.; Fenwick, S.
Abstract : Background: UK NICE guidance recommends initiation of tumour necrosis factor-alpha inhibitor (TNFi) for patients with severe RA unresponsive to intensive therapy with conventional disease-modifying anti-rheumatic drugs (cDMARD). Data comparing cDMARD and TNFi in clinical trial settings are common, but there is limited published real-world evidence on their comparative effectiveness. Objectives: Compare disease status and outcomes in UK patients with RA receiving cDMARD vs TNFi. Methods: Data derive from Adelphi's RA Disease Specific Programme 2017, a cross-sectional survey of 49 UK rheumatologists providing information on demographics, disease history, disease status and treatment of patients with RA. All patients (n=640) were included in the RA treatment analysis; patients were included in the comparative analysis if at the time of survey they had been receiving current treatment for at least 3 months, with either cDMARD (and had never received biologic(b)DMARD), or a TNFi (and had never received prior bDMARD). A propensity score based on BMI, duration on current therapy, RA severity and disease duration at initiation of current therapy was used to match treatment groups. Using Abadie-Imbens standard errors, clinical characteristics and measures of disease activity were compared between the matched groups. Results: Current therapy of 640 patients: 379 (59.2%) bDMARD, of which 253 (66.8%) were receiving TNFi; 212 (33%) cDMARD; 18 (2.8%) had never received any DMARD, 15 (2.3%) had discontinued bDMARD. Mean DAS28 at initiation of therapy was 4.94 in overall cDMARD and 5.77 in TNFi groups. Table 1 shows the comparative analysis of cDMARD vs TNFi matched treatment groups. The cDMARD group had a higher proportion of moderate/severe and active/very active disease at time of survey, a higher proportion of patients in this group had no improvement in disease severity or activity since initiation of current therapy, and they were less likely to have achieved a EULAR response. A higher proportion of cDMARD patients and physicians were not satisfied with their disease control. Mean DAS28 scores at time of survey had declined from time of initiation of therapy to time of survey in matched cDMARD vs TNFi groups, from 5.27 to 3.1 vs 5.77 to 2.7 respectively. Conclusions: UK patients with RA receiving cDMARD have poorer outcomes, in terms of measured disease status and control, than their matched counterparts receiving TNFi. Despite having a higher mean DAS score at initiation, patients in the TNFi group had a lower mean score at time of survey than patients receiving cDMARD. This real-world evidence highlights the continued utility of TNFi as effective treatments for patients with RA. Potential benefit of early TNFi initiation merits further research. Disclosure of Interest: J. Addison Shareholder of: Biogen, Employee of: Biogen, S. Lobosco Employee of: Adelphi Real World, B. Hoskin Employee of: Adelphi Real World, E. Sullivan Employee of: Adelphi Real World, J. Pike Employee of: Adelphi Real World, S. Fenwick Shareholder of: Biogen, Employee of: Biogen